2023
DOI: 10.1111/cpr.13525
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive view of macrophage autophagy and its application in cardiovascular diseases

Wanqian Pan,
Jun Zhang,
Lei Zhang
et al.

Abstract: Cardiovascular diseases (CVDs) are the primary drivers of the growing public health epidemic and the leading cause of premature mortality and economic burden worldwide. With decades of research, CVDs have been proven to be associated with the dysregulation of the inflammatory response, with macrophages playing imperative roles in influencing the prognosis of CVDs. Autophagy is a conserved pathway that maintains cellular functions. Emerging evidence has revealed an intrinsic connection between autophagy and mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 208 publications
(460 reference statements)
0
3
0
Order By: Relevance
“…TEM images suggested that the number of autolysosomes in macrophages increased after Co-ZIF-8 coincubation (Figure 4l), while RT-PCR results further revealed the upregulated expression of LC3 in these cells (Figure S12), indicating the elevated autophagy level, which was reported to be associated with the M2 polarization of macrophages (Discussion S1). 31 Journal of the American Chemical Society kit-8 assay, flow cytometry, and malondialdehyde enzymelinked immunosorbent assay kit (Figures S13−S15). To evaluate the effect of anti-inflammatory action of Co-ZIF-8 on the biological behavior of VSMCs, an indirect coculture method was applied by adding the culture medium of M1 macrophages cotreated with Co-ZIF-8 into the culture medium of MOVAS cells (Figure S16).…”
Section: Cellular Anti-inflammatory Effect Of Co-zif-8mentioning
confidence: 99%
“…TEM images suggested that the number of autolysosomes in macrophages increased after Co-ZIF-8 coincubation (Figure 4l), while RT-PCR results further revealed the upregulated expression of LC3 in these cells (Figure S12), indicating the elevated autophagy level, which was reported to be associated with the M2 polarization of macrophages (Discussion S1). 31 Journal of the American Chemical Society kit-8 assay, flow cytometry, and malondialdehyde enzymelinked immunosorbent assay kit (Figures S13−S15). To evaluate the effect of anti-inflammatory action of Co-ZIF-8 on the biological behavior of VSMCs, an indirect coculture method was applied by adding the culture medium of M1 macrophages cotreated with Co-ZIF-8 into the culture medium of MOVAS cells (Figure S16).…”
Section: Cellular Anti-inflammatory Effect Of Co-zif-8mentioning
confidence: 99%
“… 77 During the initial hours post‐MI, myocardial cells undergo swelling and necrosis, the interstitium of the myocardium becomes edematous and eosinophils infiltrate; in subsequent inflammatory phase, characterized by extensive infiltration of inflammatory cells (primarily neutrophils) into the necrotic area, activation of these inflammatory cells and death of cardiomyocytes leads to an elevation in the local and circulating concentrations of S100A9, which initiates an inflammatory cascade via triggering downstream signalling pathways and participating in the process of myocardial injury; concurrently, macrophages play a role from the inflammatory phase to the granulation tissue stage and are involved in both myocardial injury and repair processes. 78 , 79 , 80 , 81 , 82 , 83 …”
Section: Role Of S100a9 In MImentioning
confidence: 99%
“…[ 7 ] Similarly, macrophage phenotypes are closely linked to AS, and transforming M1 macrophages to M2 macrophages can have a positive impact on AS management. [ 8 ] Therefore, simultaneously scavenging ROS to reduce ox‐LDL formation, inhibiting the inflammatory response, facilitating M2 polarization of macrophages and promoting macrophage autophagy are promising treatment strategies for effectively hampering the progression of AS.…”
Section: Introductionmentioning
confidence: 99%